Analisis Kesalahan Penulisan Ejaan dalam Alternate Universe Romansa Kota Bandung Pada Platform Twitter Karya Noaprile dan Implikasinya Terhadap Pembelajaran Bahasa Indonesia Di SMP - Ida Rahmadani; Lazarus Linarto; Albertus Purwaka; Misnawati Misnawati; Syarah Veniaty (PROSIDING SEMINAR NASIONAL PENDIDIKAN, BAHASA, SASTRA, SENI, DAN BUDAYA, 2024)
The objectives of this research are (1) to explain the errors in the use of letters in "Alternate Universe Romansa Kota Bandung" by Noaprile, (2) to explain the errors in word writing in "Alternate Universe Romansa Kota Bandung" by Noaprile, (3) to explain the errors in punctuation usage in "Alternate Universe Romansa Kota Bandung" by Noaprile, and (4) to explain the implications of the analysis of spelling errors for Indonesian language teaching in junior high schools. This study employs the EYD Edition V rules to understand the linguistic rules concerning spelling. The background of this thesis is the trend of Alternate Universe among teenagers and the curiosity about various spelling errors found in the story. This research uses a qualitative methodology. The stages related to data, data forms, data sources, data collection, data analysis, and data validity in this research align with the qualitative design concept. The implementation stages include (1) pre-field stage, (2) implementation stage, and (3) completion stage. The results of this study indicate that there are spelling errors in the punctuation marks, such as periods and hyphens, in the writing of "Alternate Universe," which can hinder the readers' comprehension.